Construction and performance of the ATLAS SCT barrels and cosmic tests - Demirköz, B; Bilge Melahat Demirkoz (2007)
ATLAS is a multi-purpose detector for the LHC and will detect proton-proton collisions with center of mass energy of 14 TeV. Part of the central inner detector, the Semi-Conductor Tracker (SCT) barrels, were assembled and tested at Oxford University and later integrated at CERN with the TRT (Transition Radiation Tracker) barrel. The barrel SCT is composed of 4 layers of silicon strip modules with two sensor layers with 80 micro m channel width. The design of the modules and the barrels has been optimized for low radiation length while maintaining mechanical stability, bringing services to the detector, and ensuring a cold and dry environment. The high granularity, high detector efficiency and low noise occupancy (< 5*10^-4) of the SCT will enable ATLAS to have an efficient pattern recognition capability. Due to the binary nature of the SCT read-out, a stable read-out system and the calibration system is of critical importance. SctRodDaq is the online software framework for the calibration and also the physics running of the SCT and has been developed and tested during construction and commissioning of the detector with cosmics. It reliably measures the SCT performance parameters for each of the 6.3*10^6 channels in the SCT, identifies defects and problematic modules and writes them to an offline database for access from Athena, the ATLAS offline software framework. This dataflow chain has been exercised during the cosmics run at CERN, where a 5*10^5 cosmics sample for the combined SCT and TRT detectors was collected with a scintillator based trigger. It is now being commissioned in the ATLAS pit.